Hubungan Kondisi Sanitasi Lingkungan Rumah dengan Kejadian Reinfeksi Kecacingan pada Murid Sekolah Dasar Bandarharjo 02 - 04 Kota Semarang - Suhartono, Suhartono; Budiyono, Budiyono; Rahfiludin, M. Zen (Jurnal Kesehatan Lingkungan Indonesia, 2002)
In the same manner as the other developing countries, Indonesia also remains face the difficulties against the high prevalence rate of infectious diseases, particularly ones that related with bad environmental condition. One of them, which is usually occurred in elementary school children and have a negative effect on their growth and development, is soil transmitted helminthiasis, an infection of intestinal worm transmitted through soil or known as helminthic disease. Three kinds of them are Ascaris lumbricoides, whipworm (Trichuris trichiura), and hookworm (Necator americanus and Ancylostoma duodenale). Based on that background, this research tried to formulate the problem as follows: is there any relationship between house sanitation and the occurrence of helminthic disease reinfection on students of Bandarharjo 02-04 Elementary School? Conclusions taken from this research are: the occurrence rate of helminthic disease reinfection on Bandarharjo 02-04 Elementary School students in Semarang Regency was 48,3%, most of studentâ€™s houses (73,3%) were in a â€œnot so goodâ€ environmental sanitation condition. There was no relationship between house sanitation and the occurrence of helminthic disease reinfection on students of Bandarharjo 02-04 Elementary School (p-value > 0,05) Key words : Environmental sanitation, reinfection, soil transmitted helminths